Detection of Entamoeba histolytica and Giardia lamblia in children with diarrhea in Tikrit city - Mohammed A. Kadir; Suhair T. El-Yassin; Ali AM (Tikrit Journal of Pure Science)
Background: Entamoeba histolytica are very common protozoan parasites in Iraq and are causative agents of gastrointestinal diseases especially among children.